Parents’ premium on important child qualities - Mabekoje, Sesan O.; Azeez, Razaq O.; Shoaga, Opeyemi; Ifegbesan, Ayodeji P. (BELIA: Early Childhood Education Papers, 2024)
Inculcation of qualitative values in the children is the duties of both the home and the school. The process is expected to start from home by the parents before the school takes over. The school is to complement the home in teaching important societal qualities to produce a holistic child. To this end, this study examined important valuable qualities to be possessed by the children from the viewpoint of parents. Adopting data collected from 1237 Nigerian participants in the World Value Survey Wave 7, eleven important qualities were considered with differences determined along demographic delineation of location, highest educational qualification, marital status, religion, and ethnicity. Findings showed that the value of good manners was of foremost importance, followed by hard work and religious faith. Thrift/saving money and things was the least important value. It was revealed amongst others that location significantly affected the feeling of responsibility, imagination, religious faith, and obedience. Also, significant differences were found in good manners, hard work, religious faith by religious beliefs. Similarly, level of literacy significantly affected good manners, hard work, and unselfishness. Findings of this study have substantial implications for parenting since parents have momentous roles to play in important child qualities.